Catheter-Directed Thrombolysis Along with Mechanical Thromboaspiration versus Anticoagulation Alone in the Management of Lower Limb Deep Venous Thrombosis—A Comparative Study - Srinivas, B. C. (Int J Angiol, 2014)
Catheter-directed thrombolysis (CDT) with assisted mechanical thrombolysis is now considered as the standard of medical care for deep vein thrombosis (DVT). The study was conducted to describe the immediate and long-term (6 months) safety and effectiveness of CDT in patient with lower limb DVT compared with the routine anticoagulation alone. All 12 to 85 years old patients with recent (0–8 weeks) DVT were included. In CDT group, thrombus was aspirated mechanically and streptokinase (STK) was given along with unfractionated heparin (UFH). After 6 months, deep venous patency and postthrombotic syndrome (PTS) was assessed by using duplex ultrasound and Villalta scale, respectively. Among 51 patients with completed data, 25 patients were allocated additional CDT given for a mean duration of 108 ± 32 hours and 26 patients were allocated standard treatment alone. Grade III (complete) lysis was achieved in 37% patients and grade II (50–90%) lysis in 63% of patients. Patients with partial lysis underwent percutaneous transluminal angioplasty and/or venous stenting. After 6 months, iliofemoral patency was found in 20 (80%) in the CDT group versus 7 (23%) in anticoagulation alone group (p < 0.01). PTS was seen in 5 (20%) in the CDT group versus 19 (77%) in anticoagulation alone group (p < 0.01). We conclude that CDT and conventional manual aspiration thrombectomy are an effective treatment for lower extremity DVT. STK infusion can be safely given up to 6 days. As addition of UFH can cause thrombocytopenia, so daily monitoring of complete blood counts is needed during CDT.